2012
DOI: 10.1002/lsm.22094
|View full text |Cite
|
Sign up to set email alerts
|

Thulium‐YAG laser sialendoscopy for parotid and submandibular sialolithiasis

Abstract: Thulium-YAG laser appears to be an effective and safe technique in the treatment of salivary lithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 20 publications
1
43
0
2
Order By: Relevance
“…Raif et al described 5 stones fully fragmented and 7 prepared for extraction by mini-forceps out of 21 stones treated with this technique 40 . The thulium YAG laser was demonstrated to be effective in stone fragmentation with a low rate of complications (12.7% ductal perforations reported by Durbec et al) 41 . A pneumatic lithotripter permits the fragmentation of the stone through a CO2 gas-driven system.…”
Section: Discussionmentioning
confidence: 99%
“…Raif et al described 5 stones fully fragmented and 7 prepared for extraction by mini-forceps out of 21 stones treated with this technique 40 . The thulium YAG laser was demonstrated to be effective in stone fragmentation with a low rate of complications (12.7% ductal perforations reported by Durbec et al) 41 . A pneumatic lithotripter permits the fragmentation of the stone through a CO2 gas-driven system.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the use of Thulium-YAG laser in combination with subsequent endoscopic extraction of fragments had been evaluated as relatively safe technique of sialolithectomy. Successfulness in relation with ESWL was comparable in the parotid gland treatment and even twice higher in the submandibular salivary gland treatment [19]. Despite these optimistic results, the long-term reserved attitude towards this technique does not change very much because of existing risks of iatrogenic damage to soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The main risks with laser fragmentation seem to be duct perforation (12.7%) and thermal injury to the surrounding nerves, vessels, and soft tissue. It has also been reported that post-operative infection occurs in 7.9% of the patients [14]. …”
Section: Discussionmentioning
confidence: 99%